Compressive strengths of concrete-filled double-skin (circular hollow section outer and square hollow section inner) aluminium tubular sections. Issue 11 (August 2019) - Zhou, Feng; Young, Ben
Experimental and numerical investigations of concrete-filled double-skin aluminium stub column with a circular hollow section as the outer skin and a square hollow section as the inner skin are presented in this article. A test program was carried out to study the influences of aluminium tube geometric dimensions and concrete strength on structural performance and strength of composite columns. A series of composite columns was tested on outer circular hollow section tubes and inner square hollow section tubes; the spaces between them had been filled with concrete of different nominal cylinder strengths of 40, 70 and 100 MPa. The tubes were fabricated by extrusion using 6061T6 heat-treated aluminium alloy having a nominal 0.2% proof stress of 240 MPa. A non-linear finite element model was developed and verified against experimental results. The test and numerical results were compared with the design strengths to evaluate the applicability of the design rules in the American specifications for aluminium and concrete structures. In addition, the proposed design equations, developed by the authors for concrete-filled double-skin aluminium tubular stub columns with circular hollow section as both outer and inner skins, were used to calculate the design strengths and compared with the experimental and numerical results obtained in this study. The proposed design equations also predicted the ultimate strengths of the concrete-filled double-skin aluminium tubular stub columns accurately with circular hollow section as the outer skin and square hollow section as the inner skin.